2020
DOI: 10.4085/1062-6050-490-18
|View full text |Cite
|
Sign up to set email alerts
|

Single-Session Video and Electromyography Feedback in Overhead Athletes With Scapular Dyskinesis and Impingement Syndrome

Abstract: Context Subacromial impingement syndrome (SIS) is associated with scapular dyskinesis, or imbalanced scapular muscle activity. Evidence has shown that feedback can improve scapular control in patients with SIS. However, it is unknown whether real-time video feedback or electromyography (EMG) biofeedback is optimal for improving scapular kinematics and muscle activity during a functional task. Objective To compare the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The muscle activities were measured with a wireless surface electromyograph (EMG), the Noraxon TeleMyo 2400 T (Noraxon, USA), and processed with Myo Research XP software (MR-XP 1.07 Master Edition, Noraxon, USA). The electrodes were attached to the pitchers with shirts removed and placed on the upper trapezius, lower trapezius, serratus anterior, biceps brachii, triceps brachii, and anterior deltoid of the dominant arm [23,25]. The MVICs of the target muscles were collected for normalization of the EMG data [26,27].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The muscle activities were measured with a wireless surface electromyograph (EMG), the Noraxon TeleMyo 2400 T (Noraxon, USA), and processed with Myo Research XP software (MR-XP 1.07 Master Edition, Noraxon, USA). The electrodes were attached to the pitchers with shirts removed and placed on the upper trapezius, lower trapezius, serratus anterior, biceps brachii, triceps brachii, and anterior deltoid of the dominant arm [23,25]. The MVICs of the target muscles were collected for normalization of the EMG data [26,27].…”
Section: Methodsmentioning
confidence: 99%
“…Glenohumeral internal rotation deficit (GIRD) is believed to be one of the adaptions contributing to shoulder injuries [16,17]. GIRD has been defined as loss of internal rotation (IR) in the dominant shoulder relative to the non-dominant shoulder [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have shown that intentional attempts at repositioning the scapula prior to elevating and/or rotating the humerus, called conscious correction, increases scapular muscle activity and enhances scapular kinematics. 34,86,89 Additionally, visual feedback, [93][94][95][96][97] auditory feedback, 93,94 and kinesthetic feedback 93,94 have been shown to positively influence scapular muscle activity and positioning. Considering the scapula as a 'link' within the kinetic chain, the feedback approach may be better suited for re-establishing scapular control as it relates to the sequential activation within the kinetic chain.…”
Section: Reconsidering Treatment Approachesmentioning
confidence: 99%
“…105 Feedback may be incorporated throughout the treatment program but there is not an exclusive type to recommend considering various forms of feedback have been shown to have positive clinical influence. [93][94][95][96][97] However, it should be noted that too much feedback can be detrimental to learning as the patient becomes reliant on the knowledge of performance. 90…”
Section: Reconsidering Treatment Approachesmentioning
confidence: 99%
“…The poor anchoring of the scapula by bony attachments results in the dynamic and static stability of the scapula being largely dependent on the balanced actions of the scapular musculature (Du et al 2020 ; Kibler & Sciascia 2010 ; Kibler et al 2013 ; Michener et al 2016 ; Sahrmann 2001 ). Historically, it has generally been accepted that proper dynamic scapular stability is provided through the combined actions of the force couples of the serratus anterior and all the parts (upper, middle and lower) of the trapezius (Bagg & Forrest 1988 ; Inman et al 1944 ).…”
Section: Introductionmentioning
confidence: 99%